Fatigue properties of laser and hybrid laser-TIG welds of thermo-mechanically rolled steels - Šebestová, Hana; Horník, Petr; Mrňa, Libor; Jambor, Michal; Horník, Vít; Pokorný, Pavel; Hutař, Pavel; Ambrož, Ondřej; Doležal, Pavel (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2020)
The hybrid laser-tungsten inert gas welding technology was applied to butt weld 3-mm-thick S460MC and S700MC high-strength low-alloy steel sheets. The intent of low-current arc addition was to preheat the material to reduce extremely fast cooling rate accompanying laser welding. High-cycle fatigue tests were performed to evaluate the effect of welding conditions on fatigue behavior of S460MC and S700MC laser and hybrid welds. Both base materials exhibit approximately the same fatigue limit. However, corresponding samples with the weld behaved significantly different under cyclic loading. We demonstrated that the drop of their fatigue lifetime is caused by the combination of microstructural changes and especially by the presence of surface notches resulting from the welding process. The two series of both steels were tested to reveal the contribution of induced surface roughness and microstructural changes itself. The first one was in the as-welded condition. The second one had a smooth surface resulting from surface layer grinding after the welding. It was found, that the geometric notches created by the welding process are the determining factor in case of both tested steels. Testing of the ground samples showed, that in case of S460MC steel, the application of pre-heat did not improve the fatigue properties. On the other hand, the performed fatigue tests showed improved fatigue limit of ground series samples of the pre-heated S700MC steel, when compared with the conventional laser welding.